By its Fruits: The Spiritual Senses in Bonaventure's 'Tree of Life'. Issue 1 (2nd January 2019) - Hughes, Kevin L.
ABSTRACT: Following recent interdisciplinary interest in the 'spiritual senses' and 'spiritual sensation, ' this essay examines the Tree of Life, Bonaventure's meditations on the life of Christ, through the interpretive lens of the 'spiritual senses.' The article proposes that the spiritual senses are not thematic but architectonic and hermeneutical in this treatise. Rather than addressing the senses explicitly, Bonaventure uses them instead as principles of composition and interpretation, eliciting spiritual perception from readers as they contemplate Christ's life and death. Such a reading brings the elusive character of spiritual perception into relation with sensible and imaginative perception, reconceiving the relationship between body and soul, affect and intellect.